Impact of Mobile Learning on Self-Regulated Learning Abilities of Higher Education Students - Zang, Shulei; Shen, Xu (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study examines the influence of mobile learning (m-learning) on the self-regulated learning skills of college students using the Z-number AROMAN decision-making approach. The rapid integration of mobile technologies into educational practices has transformed traditional learning environments, offering unprecedented opportunities to enhance student autonomy and engagement. This study introduces a novel method for evaluating complex and uncertain educational scenarios through the Z-number AROMAN decision-making process. This approach provides a robust framework for assessing various intricate aspects of self-regulated learning, including goal setting (GS), self-monitoring, and reflective practices. The study underscores the transformative potential of m-learning in education, underscoring the importance of leveraging such technology to foster student-centered learning environments. This study contributes to the body of literature on educational technology, offering valuable insights for educators, policymakers, and scholars seeking to effectively implement m-learning strategies to enhance student learning outcomes.